Ecocardiografia convencional e tridimensional, deformação miocárdica e índices prognósticos em pacientes com doença pulmonar obstrutiva crônica - Claudia Myriam Amaral Botelho (2014)
Background: There is limited information in the literature about subclinical alterations of right ventricular function in COPD (Chronic Obstructive Pulmonary Disease) and its associations with severity indices of the disease. Objectives: 1) to compare conventional, 2D or bidimensional [including deformation indices, strain (S), strain rate (SR) and global longitudinal 2D strain (GLS)] and 3D or tridimensional echocardiographic (Echo) right ventricular (RV) parameters in COPD patients and controls; 2) to compare the same variables between controls and COPD subgroups: with reduced tricuspid annular plane systolic excursion (TAPSE) or GLS or right ventricular ejection fraction (RVEF) or elevated pulmonary artery systolic pressure (PASP); 3) to correlate pulmonary functional and VD echocardiographic parameters with known prognostic indices in COPD patients. Methods: 20 stable COPD patients were compared to 20 matched controls, without known cardiovascular disease, in regards to clinical evaluation, pulmonary functional tests [spirometry and six minute walk test (6MWT)] and conventional, 2D and 3D Echo. Subgroups were also compared between each other and with controls. Correlation analysis between pulmonary function parameters, VD Echo data and prognostic indices were established [BODE, BODE updated (BODEup), eBODE, BODEx, DOSE and ADO indices] in COPD patients, Results: RV end diastolic wall thickness (RVwt) was significantly thicker (6.50±1.67 x 4.40±0.53 mm, p<0.001), TAPSE was lower (18.0±3.7 x 21.5±3.1 mm, p=0.002); PASP was higher (43.2±11.02 x 25.4±2.87, p<0.001) in COPD patients than in controls. All deformation indices were reduced in COPD patients, especially GLS (-16.2: -10.9/ -27.8 x -21.8:-16.2/- 24.2 %, p=0.001). Right ventricular stroke volume (RVsv, 24.8±10.1 x 32.3±8.9 ml, p=0.022) and RVEF (40.8±9.4 x 51.1 ± 6.4 ml, p<0.001) were also reduced in these patients. Subgroups of COPD patients showed the same differences as the total group. Mean MMRC Dyspnea score in this sample of COPD patients, was 1.5 (0-4), 70% were severely or very severely obstructed, 80% were from C or D groups and 55% had more than one exacerbation in the preceding year; Mean severity/prognosis indices scores were: BODE= 3.7±2,7; BODEup= 2.5 (0-13), eBODE= 4.7±3.1, BODEx=4.1±2.3, DOSE= 2.6±1.8, ADO= 4.5±1.8. Correlation analysis between severity/prognosis indices and echo variables did not correlate well, except TRV and PASP, which correlated at least moderately with all indices. Sb (basal strain) was inversely correlated with four indices (r=-0,456 to -0,570; higher p=0,043) and GLS with just BODEup ( r=-0,453 e p=0,045). Conclusions: All myocardial deformation indices (mainly SLG), RVsv and RVEF were robust markers of RV dysfunction and its prognostic implications in COPD patients. TAPSE, RVwt, TRV and PASP could also distinguish COPD RV hypertrophy and dysfunction, but no measurement of right ventricular dimensions could. RV echo parameters were poorly correlated with multidimensional indices and they could be included in future indices to improve prognosis and define therapeutical strategies.